Mengelaborasi Definisi Variatif dan Penempatan Jenis Pendidikan Kristiani Pada Lembaga Pendidikan - Hasudungan Simatupang (Jurnal Christian Humaniora, 2023)
The purpose of this study is to find out the various definitions and placements of the three types of Christian education based on the New Testament in formal, informal and non-formal educational institutions according to the levels and educational programs needed by Christians.This type of research is qualitative in order to elaborate and present data/information about various definitions consisting of three types of education namely: Christian Education, Christian Religious Education, Religious Education of Christianity which takes place in educational institutions within churches, theological schools and public schools.This research method is descriptive which seeks to present data or information and an overview of the results of the elaboration and clarification of the various definitions that affect the placement of the three types of Christian education at the level of general and theological educational institutions in Indonesia.The results of the study present a definition according to the New Testament, especially the Synoptic Bible as a reference to define: First, Christian Education and the educational institutions in it consist of Sunday School, Bible School, Evangelism School, Bible Course, Bible Teacher School (Congregational Teacher), Baptist Catechism, Biblevrow School, Church Elder/Worker Candidate School, Deaconess School. Second, Christian Religious Education consists of: Early Childhood Education or Christian Theological Kindergarten, Christian Theological Elementary School, Christian Theological Middle School, Christian Theological Middle School and Christian Theological College or Christian Religious Education College. Third: Religious Education of Christianity consists of: Early Childhood Education, Kindergartens, Elementary Schools, Junior High Schools, High Schools, Public Universities.